Faith, Politics, and Democracy: Unraveling Historical and Contemporary Dynamics in Religious Influences on Electoral Processes - Maspul, Kurniawan Arif (Religion and Policy Journal, 2023)
Research Problem: This qualitative research addresses the intricate relationship between religion, politics, and societal dynamics, focusing on historical contexts in the early 7th century Islamic Caliphate and contemporary Saudi Arabia. It aims to understand how religion influences political decisions and societal structures, both historically and in the present day. Research purposes: The primary purpose of this study is to analyze the spread of Islam's impact on governance and societal norms, particularly examining the dominance of Islamic governance in the early 7th century Caliphate and its evolution over time. Additionally, it seeks to empirically demonstrate the role of religious authorities in shaping governmental policies in contemporary Saudi Arabia. Research methods: Methodologically, this research employs qualitative analysis techniques, utilizes unique datasets, and adopts a comparative approach. It delves into historical records and contemporary observations to uncover nuanced interactions between religious institutions and political choices. Results and Discussion: The study reveals the historical dominance of Islamic governance and its subsequent evolution due to various societal and political movements. It also provides empirical evidence of the significant role religious authorities play in shaping governmental policies in contemporary Saudi Arabia, particularly in social and legal frameworks. The research discusses the influence of religious leaders on their followers and explores the role of clerics in shaping public opinion and political participation. Research Implications and Contributions: This study has several implications and contributions. Firstly, it enriches our understanding of the intricate dynamics between Islam and politics, offering valuable insights into the historical depth and contemporary significance of this interconnected relationship. Secondly, it contributes to comparative political research by reflecting on the enduring legacy of Huntington's clash of civilizations thesis, highlighting the ongoing relevance of religious influences in Middle Eastern political systems. Finally, it sheds light on the role of religious authorities in shaping governmental policies and societal norms, emphasizing the importance of considering religious dynamics in political analyses and decision-making processes.